2010
DOI: 10.1021/cb100177g
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Drug Target Flexibility Using in Situ Click Chemistry: Application to a Mycobacterial Transcriptional Regulator

Abstract: In situ click chemistry has been successfully applied to probe the ligand binding domain of EthR, a mycobacterial transcriptional regulator known to control the sensitivity of Mycobacterium tuberculosis to several antibiotics. Specific protein-templated ligands were generated in situ from one azide and six clusters of 10 acetylenic fragments. Comparative X-ray structures of EthR complexed with either clicked ligand BDM14950 or its azide precursor showed ligand-dependent conformational impacts on the protein ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 33 publications
(38 reference statements)
4
78
0
Order By: Relevance
“…These structures have been critical in the design of synthetic EthR ligands (see below), and subsequent structures of EthR have been solved in complex with a number of these molecules (63)(64)(65). In one study, two related analogs were found to bind EthR with different orientations, supporting the extremely plastic nature of the EthR ligand-binding pocket (63).…”
Section: Tfr-ligand Interactionsmentioning
confidence: 98%
“…These structures have been critical in the design of synthetic EthR ligands (see below), and subsequent structures of EthR have been solved in complex with a number of these molecules (63)(64)(65). In one study, two related analogs were found to bind EthR with different orientations, supporting the extremely plastic nature of the EthR ligand-binding pocket (63).…”
Section: Tfr-ligand Interactionsmentioning
confidence: 98%
“…The in situ formed inhibitor, displayed 10-fold higher activity than the starting azide, and induced a significant conformational change of the ligand-binding domain of EthR. 145 …”
Section: Dna Minor Groove Templation Rolementioning
confidence: 98%
“…ase, [14][15][16][17] carbonic anhydrase, [18][19][20][21] human immunodeficiency virus (HIV)-1 protease, 22) Serratia marcescens chitinase (SmChi), [23][24][25] Mycobacterium tuberculosis EthR protein, 26) Akt1, 27) acetylcholine binding protein, 28) G-Quadruplex 29) and biotin protein ligase inhibitors 30) have served as templates. Here, we report in situ click chemistry approaches, focusing on hDAO as the target enzyme to generate novel hDAO inhibitors.…”
Section: This Article Is Dedicated To Professor Satoshi ōMura In Celementioning
confidence: 99%